Effect of radio frequency tempering on the color of frozen tilapia fillets. (May 2021) - Jiang, Jiwei; Wang, Hongli; Guo, Xueqian; Wang, Xichang
Abstract: Radio frequency (RF) processing has been widely used for thawing and tempering of frozen products for further processing and consumption. RF tempering could improve the color and other qualities compared with traditional methods, but the specific mechanism to ensure the color is not clear. Effect of different RF treatments on the color of frozen tilapia fillet was to investigate in this study. The color of tempered tilapia fillets under different RF conditions (based on power (300, 600, 900 W) and electrode gap (10, 12, 14 cm)) and the myoglobin oxidation, lipid oxidation, and moisture migration and other influencing factors on color were determined. Relationships between relative impact indicators and color attributes were investigated by multivariate analysis (visual network analysis). The results showed that hue angle and whiteness between 600 W and other power had significant differences under the electrode gap of 10 cm and 14 cm. The difference in color attributes under different RF tempering conditions had a relatively strong correlation with pH, migration of bound water to immobilized water, content of immobilized water, and drip loss during RF tempering. Besides, the difference of color attributes weakly correlated with myoglobin oxidation and lipid oxidation during RF tempering. Highlights: The color after RF tempering correlated strongly with the content of immobilized water. pH and drip loss have a strong effect on the color of fillets after RF tempering. Lipid oxidation and myoglobin oxidation weakly affect color after RF tempering.